Challenges and possibilities of intravascular cell therapy in stroke - Rissanen, Anna; Jolkkonen, Jukka (My University, 2009)
Stroke is the third leading cause of death in Western countries and more importantly a leading cause of adult disability. The recovery process of stroke patients might be enhanced by intensive rehabilitation, which acts through brain plasticity mechanisms. Restorative approaches such as cell-based therapies are clinically appealing as it might be possible to help patients even when treatment is initiated days or weeks after the ischemic insult. An extensive number of experimental transplantation studies have been conducted with cells of different origins (e.g., embryonic stem, fetal neural stem, human umbilical cord blood) with promising results. Noninvasive intravascular administration of cells, which provides a broad distribution of cells to the close proximity of ischemic tissue, has perhaps the most immediate access to clinical applications. However, surprisingly little is known about whole body biodistribution of intravascularly administered cells and mechanisms leading to improved functional recovery. This review examines the recent literature concerning intravascular cell-based therapies in experimental stroke.
Keywords: biodistribution; experimental cerebral ischemia; functional recovery; intravascular administration; mechanism